2022
DOI: 10.1111/jcms.13345
|View full text |Cite
|
Sign up to set email alerts
|

Euroscepticism, Anti‐Nostalgic Nostalgia and the Past Perfect Post‐Brexit Future

Abstract: While extant work on British Euroscepticism has highlighted vestiges of historical empire imaginaries in discourses opposing EU integration, the emotional dynamics of such frames remain curiously underexplored. The diluted quality of these Eurosceptic histories, with their distinctive interplay of past and future, has led some to reject their nostalgic emotional credentials altogether. This article challenges such assumptions of emotional absence through a qualitative discourse analysis of the 2016 EU referend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Powellite nostalgia, then, manifests specifically as a desire to restore the racial homogeneity of England and preserve the qualities of white Englishness from the existential threat of a supposed immigration 'crisis'. Although Powellite nostalgia is rooted in the experiences of empire, it is distinct from the 'outward-facing' and superficially 'anti-nostalgic' imperial and colonial nostalgias associated with the Global Britain discourse (Melhuish, 2022), finding emotional resonance instead in the 'inward-looking' but imperially-inflected imaginaries of a domesticated Little England.…”
Section: Powellite Nostalgia As Control and Colonial Authoritymentioning
confidence: 99%
See 2 more Smart Citations
“…Powellite nostalgia, then, manifests specifically as a desire to restore the racial homogeneity of England and preserve the qualities of white Englishness from the existential threat of a supposed immigration 'crisis'. Although Powellite nostalgia is rooted in the experiences of empire, it is distinct from the 'outward-facing' and superficially 'anti-nostalgic' imperial and colonial nostalgias associated with the Global Britain discourse (Melhuish, 2022), finding emotional resonance instead in the 'inward-looking' but imperially-inflected imaginaries of a domesticated Little England.…”
Section: Powellite Nostalgia As Control and Colonial Authoritymentioning
confidence: 99%
“…Yet Global Britain's persistent association with the British empire and race mean that it is not simply English nationalism's more palatable sibling. Scholars have only recently begun to unpack the racial dimensions of the Global Britain discourse, including its thinly-veiled preference for limited, culturally compatible forms of immigration (Namusoke, 2016(Namusoke, , 2019 and its entanglement with imperial and colonial nostalgias, defined, respectively, as a desire to rehabilitate the political economic benefits of Britain's world role and resurrect comforting relationships with its former white settler colonies (Melhuish, 2022).…”
Section: Revisiting Englishness and Empirementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the first point, it is important to note that whilst not all member states would narrate the EU as positively as Germany did, and not all of their histories are as deeply intertwined, they nonetheless have to navigate EU narratives and resort to Gefühlspolitik. For example, during the Brexit campaign, the EU was narrated as having disrupted the UK's path and was deeply rooted in an affectively appealing nostalgia (Melhuish, 2022; see also Browning, 2019); more generally, research has shown that framing the EU emotionally resonates stronger with audiences (Atikcan, 2015;Atikcan et al, 2020). Moreover, analysing the case of Germany allows us to bring a comparative angle and demonstrate how the same narrative was strategically used within a short timeframe to justify two starkly different positions: the pro-refugee 'open-door policy', and the backing of the EU-Turkey deal.…”
Section: Affective Narratives and Memorymentioning
confidence: 99%
“…These are often in the form of ostentatious self‐affirming proclamations, attributing to the post‐Brexit future positive qualities such as ‘great’, ‘bright’ and ‘prosperous’ (Brusenbauch Meislová, 2019). The UK government frequently appeals to a nostalgic vision of the UK's role as a ‘proud trading nation’, tapping into British aspirations to be acknowledged again as a great power (Freedman, 2020; Melhuish, 2022).…”
Section: Three Temporal Regimes Of Brexit Discursive Legitimation: An...mentioning
confidence: 99%